Перспективы освоения железорудных месторождений Томской области - Мазуров А. К. Алексей Карпович; Боярко Г. Ю. Григорий Юрьевич; Ананьев А. А. Анатолий Анатольевич; Емешев В. Г. Владимир Георгиевич (2005, 2005)
Заглавие с экрана